(untitled) (Linguostylistic Studies, 2015)
In the article the understanding of ‘concept’ as reflections of presentations aggregate of separate individual and the whole ethnos is considered. This understanding is observed about confident cultural segment in a verbalized form, which combines linguistic, psychological and cultural factors. Essence of national cultural space is investigated as information and cognitive environment of information code where of the system of cultural codes is developed. Basic conceptual components of Ukrainian national cultural space are determined in the article; these components are submitted in the philosophical poem-clip by Stanislav Bondarenko «Night conversation with Europe». In particular, it is found out that in the language of poem of Stanislav Bondarenko basic sign conceptual formations are presented by all spheres of life of the Ukrainian people, namely: history, science, language and written language, literature, art, public life. The role of word images that are analysed is determined in the creation of the stylistic ideostyle system of Stanislav Bondarenko. Key words: concept, conceptosphera, national cultural space, mikrosphere, intertextuality, precedent name. References